Kedudukan Hukum dan Fungsi Surat Edaran Kapolri Nomor. SE/7/VII/2018 tentang Penghentian Penyelidikan - Muhammad Huzaini; Deni Setya Bagus Yuherawan (Universitas Widya Gama Malang, 2021)
This article reviews the Circular of the Chief of Police of the Republic of Indonesia Number: SE / 7 / VI / 2018 concerning the termination of the investigation. The emergence of this circular provides legal certainty value for alleged criminal acts with inadequate facts and evidence so that the investigation must be stopped. On the one hand, it also degrades the value of legal certainty because it forms a new norm regarding the termination of investigations which is not regulated at all in the Criminal Procedure Code as a formal legal basis in criminal law. The author is interested in reviewing the Chief of Police circular in terms of statutory regulations and functions. This paper is theoretical research with a conceptual approach. The results of this research are the legal position of the Chief of Police Circular Number: SE / 7 / VII / 2018 concerning the Termination of Investigation is not included in the laws and regulations. The function of the Chief of Police Circular Number: SE / 7 / VII / 2018 concerning the Termination of Investigation to fill the legal vacuum regarding the mechanism for terminating the investigation which is not regulated in the Criminal Procedure Code and the function of the Chief of Police Circular Letter No: SE / 7 / VII / 2018 concerning the Termination of Investigation is as instructions and notifications regarding the mechanisms and procedures for terminating investigations to investigators of the Indonesian National Police. AbstrakArtikel ini mengulas Surat Edaran Kapolri Nomor: SE / 7 / VI / 2018 tentang penghentian penyelidikan. Munculnya surat edaran ini memberikan nilai kepastian hukum atas dugaan tindak pidana dengan fakta dan bukti yang tidak memadai sehingga penyelidikan harus dihentikan. Di satu sisi juga merendahkan nilai kepastian hukum karena membentuk norma baru mengenai penghentian penyelidikan yang sama sekali tidak diatur dalam KUHAP sebagai landasan hukum formal dalam hukum pidana. Penulis tertarik untuk mengkaji surat edaran Kapolri ditinjau dari peraturan perundang-undangan dan fungsinya. Makalah ini merupakan penelitian teoritis dengan pendekatan konseptual. Hasil penelitian ini adalah kedudukan hukum Surat Edaran Kapolri Nomor: SE / 7 / VII / 2018 tentang Penghentian Penyelidikan tidak termasuk dalam peraturan perundang-undangan. Fungsi Surat Edaran Kapolri Nomor: SE / 7 / VII / 2018 tentang Penghentian Penyelidikan untuk mengisi kekosongan hukum mengenai mekanisme penghentian penyelidikan yang tidak diatur dalam KUHAP dan fungsi Kepala Badan Reserse Kriminal. Surat Edaran Kepolisian No: SE / 7 / VII / 2018 tentang Penghentian Penyelidikan sebagai petunjuk dan pemberitahuan mengenai mekanisme dan prosedur penghentian penyelidikan kepada penyidik Kepolisian Negara Republik Indonesia.